Податкова система України: поняття та перспективи розвитку - Товкун, Л.; Tovkun, L. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Предметом дослідження статті є податкова система, а також принципи, на основі яких вона функціонує. В статі дається характеристика податкової системи, як складної категорії податкового права. Зазначається необхідність більш широкого її визначення у порівнянні з тим, що є у Податковому кодексі України. Визначаються шляхи реформування податкової системи, опираючись на діючі та нові принципи функціонування податкової системи. The object of research of the article is the taxation system of Ukraine. Its functioning is connected with certain problems and contradictions. The development of the taxation system is defined by the level which the state reached in economic, political and social spheres. Despite the constant interest and rather high level of research of this subject, many debatable questions still exist. Actuality of the subject has been defined by the fact that the taxation system is the basis for satisfying the functioning of public expenses. The development of economy and attraction of investments into all spheres of a national economy depends on the development of the taxation system. Characterizing the concept of «taxation system» the author finds it necessary to emphasize its complicated structure. As one of the elements of the taxation system the principles of its functioning can be defined. It is especially important during overwhelming changes in society when legislation remains behind the requirements of social development, and sometimes contradicts new values. A special place among the principles of the taxation system is taken by the principle of social justice and the principle of equality of all payers before the law. Considering the changes in the taxation system of Ukraine, the list of the principles can be expanded. But it ought to be not formal increase of the principles, but the development of them on the basis of thorough analysis of the national legal system and taxation practice.
Taxation System of Ukraine: Concept and Prospects of Development
Keywords: податкова система; принципи податкової системи; платник податків; контролюючі органи; податки; taxation system; principles of the taxation system; taxpayer; supervisory authorities; taxes